Inefisiensi Penerbitan Kartu Nikah Fisik pada Layanan Publik di Kantor Urusan Agama (KUA) - Merdeka, Ihsan Bayu (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2024)
Marriage registration services are a mandate carried out by the Ministry of Religious Affairs, particularly through the Office of Religious Affairs (KUA). For each marriage event, in addition to being recorded in the marriage certificate, it is also provided in the form of a book submitted after the marriage ceremony. In 2018, the Ministry of Religious Affairs issued the Marriage Card as a complement to the marriage book, considering it would facilitate the mobility of couples as authentic proof of marital status. In practice, approximately 2 million marriage cards are distributed each year, with budget assumptions for the procurement of card printing machines amounting to IDR 118.9 billion, which would be fulfilled in at least nine years. The annual printing cost is IDR 21.9 billion, with maintenance costs of IDR 2.9 billion per year. The objective of this policy paper is to evaluate the efficiency of budget utilization related to the issuance of physical marriage cards, with a focus on annual distribution, printing costs, and maintenance. Additionally, this policy paper employs a quantitative method to reveal the importance of careful budget management in supporting quality and accountable public services. The research concludes that the issuance of physical marriage cards is inefficient from a budgetary perspective and could result in a massive financial burden. Furthermore, the policy paper recommends an alternative solution through the utilization of digital cards, adapting to the technological needs of the tech-savvy millennial generation.